2014
DOI: 10.1016/j.jams.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nausea Control by Needling at Acupuncture Point Neiguan (PC6) During an Intraoral Impression-Taking Procedure

Abstract: The objective of this study was to evaluate the effectiveness of acupuncture point PC6 (Neiguan) in controlling nausea during intraoral impression taking. This study was conducted in Piracicaba, São Paulo, Brazil. The sample consisted of 33 adult volunteers with nausea, who were randomly divided into control and study groups, and treated with nonpenetrating sham acupuncture and real acupuncture, respectively, at acupoint PC6. The two groups had two maxillary impressions taken, one prior to acupuncture and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Gagging problems are not uncommon in daily dental practice and the exact prevalence is unknown. This can have an important impact on treatment plan and dental treatment outcome [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gagging problems are not uncommon in daily dental practice and the exact prevalence is unknown. This can have an important impact on treatment plan and dental treatment outcome [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, they indicated that PC-6 point was effective for controlling gaging reflex during preparing maxillary impression procedure. [ 13 ] The PC-6 point was again observed by Rahshenas et al . [ 19 ] They examined the acupuncturing of that point for eliminating the induced gaging during stimulation of the soft palate and the sides of the tongue by medical wood sticks.…”
Section: Discussionmentioning
confidence: 56%
“…From the gathered articles, 8 of them[ 12 13 14 15 16 17 18 19 ] met the inclusion criteria in which 6 of them were indexed on PubMed database. [ 12 13 14 15 16 17 ] Nevertheless, 2 of mentioned studies were case-series. [ 16 17 ] The three of them used the pericardium-6 (PC-6) point and two of them used Conception vessel 24 (CV-24) acupuncturing points.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis has demonstrated that acupuncture to this point significantly decreased gagging compared to sham acupuncture to the same point. 11,19 In a randomised double-blind study acupuncture to P-6 improved visual analogue scores (VAS) by 48% (p = 0.0015) in addition to improving GSI and GPI scores by 32% (p = 0.0016). 20 Similar results have been established by other researchers, acupuncture to P-6 exhibited an average mean score of 0.92 (p <0.001) compared to pseudo-acupuncture to the same point which showed a mean score of 1.37 (p = 0.157).…”
Section: -18mentioning
confidence: 99%